Three new species of Atkinsoniella from China (Hemiptera: Cicadellidae: Cicadellini) - Meng, Ze-Hong; Yang, Mao-Fa; Ni, Jun-Qiang (Zootaxa, 2010)
Three new species of Atkinsoniella Distant, 1908 from China are described and illustrated: A. biundulata sp. nov., A. cuspidata sp. nov., and A. motuoensis sp. nov. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China, except for A. motuoensis, which is deposited in the Shanghai Entomological Museum, Chinese Academy of Sciences.